β-cyclodextrin/isopentyl caffeate inclusion complex: synthesis, characterization and antileishmanial activity - Marques, Carine S. F. (2020)
Isopentyl caffeate (ICaf) is a bioactive ester widely distributed in nature. Our patented work has shown promising results of this molecule against Leishmania. However, ICaf shows poor solubility, which limits its usage in clinical settings. In this work, we have proposed the development of an inclusion complex of ICaf in -cyclodextrin (-CD), with the aim to improve the drug solubility, and thus, its bioavailability. The inclusion complex (ICaf:-CD) was developed applying three distinct methods, i.e., physical mixture (PM), kneading (KN) or co-evaporation (CO) in different molar proportions (0.25:1, 1:1 and 2:1). Characterization of the complexes was carried out by thermal analysis, Fourier-transform infrared spectroscopy (FT-IR), scanning electron microscopy (SEM) and molecular docking. The ICaf:-CD complex in a molar ratio of 1:1 obtained by CO showed the best complexation and, therefore, was selected for further analysis. Solubility assay showed a marked improvement in the ICaf:-CD (CO, 1:1) solubility profile when compared to the pure ICaf compound. Cell proliferation assay using ICaf:-CD complex showed an IC50 of 3.8 and 2.7 µg/mL against L. amazonesis and L. chagasi promastigotes, respectively. These results demonstrate the great potential of the inclusion complex to improve the treatment options for visceral and cutaneous leishmaniases.